Faktor-Faktor Yang Dipertimbangkan Konsumen Untuk Menjadi Nasabah Tabungan - Andika Putra, I Putu Yudi; Ekawati, Ni Wayan (E-Jurnal Manajemen, 2013)
This study was conducted to determine the factors that consumers consider to be customer savings on PT. Regional Development Bank Branch Sanur Bali. Accidental sampling method is used to take samples in this study, the analysis technique used is exploratory factor analysis and processing of data using SPSS for windows 13:00. These results indicate that the factors that consumers consider to be saving clients are psychological factors, people factors, promotional factors, product factors, cultural factors, and personal factors.   Keywords : psychology, people, promotion, product, culture, personal.